(untitled) (Al-Aasar, 2026)
In the early age of Islam, many Muslim scientists explored and analyzed the natural world. They did it to get a deeper understanding and recognition of Allah (SWT), considering the study of nature an act of worship. In this article I analyses Muslim scholars, Al-Jāhiz, Al-Bīrūnī, and Ibn Bassāl about how they examined the natural world and its systems in a systematic and scientific manner. Their works carry significant value and can provide useful insights for modern ecological problems. By reviewing their research, methodologies, and environmental insights, modern scientists may develop more holistic and ethically grounded approaches to solving today’s ecological crises.